Feasibility study on proposed Master in Landscape Architecture Program for the Department of Landscape Architecture, FSPU / Abd. Haris Shamsuddin, Alamah Misni and Prof. Madya Anuar Mohd Noor - Shamsuddin, Abd. Haris; Misni, Alamah; Mohd Noor, Anuar (Institute of Research, Development and Commercialization (IRDC), 2006)
The Faculty of Architecture, Planning and Surveying at the Universiti Teknologi MARA was set up in 1967 as the School of Applied Arts. The School was separated into two art-based different schools in 1971, which was then set with a new name as the School of Art and Architecture. Over the time, the School has been upgraded and now known as the Faculty of Architecture, Planning and Surveying (FSPU). It has been significantly expanded and the curriculum offers a broad range of study in built environment including architecture; interior architecture; landscape architecture; building surveying; town and regional planning; estate management; building; construction and project management; quantity surveying; geomantic science; and parks & amenity management. As part of the government aspiration of the university towards 200,000 enrolments in year 2015, the faculty is continuously expanding and increases its students. The number of programs offered amplify from four in 1967 to twenty eight in 2006. These include the under graduate, graduate and post graduates level of built environment programs.